Cross-sectional association between social and demographic factors and disease activity in rheumatoid arthritis - Lei Zhu; Larry W. Moreland; Dana Ascherman (BMC Rheumatology, 2024)
Abstract Background This study aimed to assess the association between social factors, demographic parameters, and disease activity among rheumatoid arthritis (RA) patients. Methods The University of Pittsburgh Rheumatoid Arthritis Comparative Effectiveness Research (RACER) registry was used for this study and included patients meeting 1987 ACR criteria for RA enrolled between 2010–2015. The registry collected clinical and laboratory data at each visit, permitting the calculation of disease activity measures that included Disease Activity 28-C Reactive Protein (DAS28-CRP). The current study was conducted as a cross-sectional study in which baseline data were used to construct multiple logistic regression models assessing the relationship between disease activity measures (DAS28-CRP), functional capacity (health assessment questionnaire (HAQ)), selected demographic and social factors (occupation, education, income, marital status, race, gender, age, and BMI), and clinical/laboratory variables. Results The analyses included 729 patients with baseline DAS28-CRP and social/demographic data. The mean age at enrollment was 59.5 (Standard Deviation (SD) = 12.7) years, 78% were female, and the median RA disease duration was 9.8 (Interquartile Range (IQR): 3.7, 19.1) years. We dichotomized the DAS28-CRP score and defined scores above or below 3.1 as high versus low RA disease activity. Most patients with high RA disease activity (N = 326, 45%) had less than a college degree (70%), were not working/retired/disabled (71%), and had an annual income under $50 K (55%). We found that higher body mass index (BMI) (Odds Ratio (OR) = 1.04, 95% CI: 1.01—1.08), longer disease duration (> 2 and < 10 years versus ≤ 2 years of disease) (OR = 0.45, 95% CI: 0.25—0.78), and being retired (OR = 1.74, 95% CI: 1.02—2.98) were associated with RA disease activity. Conclusion Increased RA activity may be associated with various social factors, potentially leading to more severe and debilitating disease outcomes. These findings provide evidence to support efforts to monitor disparities and achieve health equity in RA.